Multi-rigid-body modeling and simulation of perimodiolar cochlear electrode arrays. (May 2019) - Zhu, Ruifeng; Li, Jianjun; Wang, Zuo; Wu, Yongzhen; Wang, Binrui; Zhao, Kai
This study presented a method that decomposes perimodiolar electrodes into multi-rigid bodies for the study on the shape variation of cochlear perimodiolar electrode. The coordinates of electrode array were obtained by capturing the shape varying image of the perimodiolar electrodes with the stylet extracted. Subsequently, the increment of the angle variation and the length of each link were obtained. Fourier compensation fitting method was developed using the three fitting methods to compare and analyze the increment of the angle variation of the perimodiolar electrode multi-rigid model. This can not only ensure that the initial angle of the joint is consistent with the actual angle of the perimodiolar electrode, but also fully reflect the varying trend of the joint angle of the multi-rigid model of the perimodiolar electrode. The simulation of the shape variation of the perimodiolar electrode multi-rigid-body model was performed using this method in the ADAMS simulation platform. According to the simulation results, the precise and continuous shape variation of perimodiolar electrodes can be obtained using this method.